(untitled) (Raparin Journal of Humanities (RJH), 2024)
The aim of this research knows the professional obstacles among the students of the College of Basic Education in the views of the teachers and school principals, as well as to know the professional obstacles among students of the College of Basic Education. For achieving the goals, the researcher used descriptive methods because it is possible with the nature of this studying. The consistencies of this research are preparing averages from the students’ professional challenges in College of Basic Education. It consists of (46) topics, dividing on (9) parts. After Assurance of this average, it has done on a part of research. This part of the research consist of (70) supervisors in both College of Basic Education in Suleimani and Charmo university. (110) school managers in both West Suleimani and Chamchamal educational directorate to solve the collective Data and Statistics in this research. The researcher used (Spss) program for the all Data. 1- It is found that the professional obstacles among the students of the College of Primary Education in the subject of vision and practice are at a high level. 2- There is a statistical difference in the views of supervising teachers and school principals for professional obstacles among students of the College of Primary Education according to the gender variable (male and female). • There is a statistical difference in the views of supervising teachers and school principals for professional obstacles among students of the College of Primary Education in terms of vision and practice according to the variables of degrees (Diploma, Bachelor’s, Master’s, PHD). 4- There is a statistical difference in the views of supervising teachers and school principals for professional obstacles among students of the College of Primary Education according to the variable years of service.